Criminal Protection of Public Personal Information in the Digital Era - Zhong, Yuxuan (Transactions on Social Science, Education and Humanities Research, 2024)
The digital era has accelerated the speed and breadth of information dissemination. While enjoying the information dividend, the security of personal information has hidden dangers of leakage. For public personal information, this concern is even worse. On the theoretical level, the secondary authorization theory, the purposiveness theory, and the objective openness standard theory cannot fully respond to the reality and urgency of repeated violations of public personal information. On the level of judicial practices, the guiding cases of personal information protection issued by the Supreme People’s Court enlighten us that we should give classified protection to public personal information. Typed protection mode classifies the public personal information from the perspectives of voluntary disclosure, compulsory disclosure, and illegal disclosure, and considers whether it is convicted or not from three aspects: the subjective illegality of the doer, the scope of information control of the information subject and the measurement of public and private interests, which strengthens the protection of the public personal information.